Design, Synthesis, Characterization, and Anti-Cancer Activity Evaluation of Novel Thiosemicarbazide Analogs - Kumar, Akhalesh; Mishra, Rakhi; Mazumder, Rupa; Mazumder, Avijit (Indian Journal of Pharmaceutical Education and Research, 2023)
Aim/Background: Across the world disease of cancer is one of the factors of death and to identify the emerging role of thiosemicarbazide analogs for the cancer disease it was decided to design, and synthesize novel thiosemicarbazide derivatives (5a-i) with in-vitro anticancer activity evaluation. Materials and Methods: Substituted benzoic acid, thionyl chloride, hydrazine hydrate, and ammonium thiocyanate were used to create a new series of thiosemicarbazide derivatives (5a-i). The final derivatives were characterized using 13C and 1H NMR, FTIR, and mass spectroscopy. The compounds were then analyzed for anticancer action with the in-vitro MTT assay method as well as by measuring the percentage of tumor growth on the B16F10 melanoma cell line, a clone of B16 cells. Results: Compounds 5a, 5b, and 5e outperformed and were comparable to the reference drug, doxorubicin. All three compounds have an electron-withdrawing group substitution and have shown remarkable anticancer effects. When compared to other substituted derivatives, the drug-likeness score evaluated by Swiss ADME online software confirmed the same fact that thiosemicarbazides with electron-withdrawing groups substitution like halogens, and nitro groups at different positions could work as excellent and promising anticancer agents. Conclusion: The study and the result of the study revealed that thiosemicarbazide moiety represents an important core and could be used as a template for further development of analogs having promising anti-cancer effects.
Keywords: Anticancer; B16F10 cell line; Melanoma; Thiosemicarbazide; MTT assay